The Influence of the Sharia Maqasid Index Forming Factors on Bank Profitability - Moch. Edman Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The aim of this research is to see the effect of the forming factors of the sharia maqasid index on profitability. research data consists of 80 years of observations obtained from bank annual reports, with warp-PLS as a data analysis tool used in this study. the variables used are education, justice, and maslaha as independent variables and return on assets as the dependent variable. the results of the study state that education has no effect on profitability, because investment in Islamic banking is still not significant for increasing stakeholder knowledge of Islamic financial literacy. Justice has a significant negative effect on profitability, occurring because financing risks are shared between Islamic banks and financing customers. Maslaha has a significant positive effect on profitability, because the role of Islamic banking in increasing welfare can be accepted by the community, which will increase acceptance of Islamic banking products in society, and will ultimately increase bank profitability.